Kadmos : Zeitschrift für vor- und frühgriechische Epigraphik (De Gruyter, 1962)
Kadmos is a journal publishing papers and communications (but no reviews) relating to pre-Greek and early Greek epigraphy, i. e. to inscriptions from the whole of the Mediterranean area dating back either 1) to the time before or during the spread of Greek in the relevant regions or 2) to the early phase of the development of Greek (in Linear A, Linear B or an archaic alphabetic script).